Effect of a concussion on subsequent baseline SCAT performance in professional rugby players: a retrospective cohort study in global elite Rugby Union - Eanna Falvey; Gordon Fuller; Martin Raftery; James Craig Brown; Ross Tucker (BMJ Open)
Objectives This study assessed whether concussion affects subsequent baseline performance in professional rugby players. Annual baseline screening tests are used to guide return-to-play decisions and concussion diagnosis during subsequent screens. It is important that baseline performances are appropriate and valid for the duration of a season and unaffected by factors unrelated to the current head impact event. One such factor may be a concussion following baseline assessment.Setting The World Rugby concussion management database for global professional Rugby Union.Participants 501 professional rugby players with two baseline Sports Concussion Assessment Tools (SCATs) and an intervening concussion (CONC) were compared with 1190 control players with successive annual SCAT5s and no diagnosed concussion (CONT).Primary and secondary outcome measures Symptom endorsement, cognitive and balance performance during annual SCAT baseline assessments.Results Players with a diagnosed concussion (CONC) endorsed fewer symptoms (change −0.42, 95% CI −0.75 to −0.09), and reported lower symptom severity scores during their second assessment (T2, p<0.001) than non-concussed players (CONT). Concussed players also improved Digits Backward and Final Concentration scores in T2 (p<0.001). Tandem gait time was improved during T2 in CONT. No other sub-mode differences were observed in either group.Conclusions Reduced symptom endorsement and improved cognitive performance after concussion may be the result of differences in the motivation of previously concussed players to avoid exclusion from play, leading to under-reporting of symptoms and greater effort in cognitive tests. Improved cognitive performance may be the result of familiarity with the tests as a result of greater exposure to concussion screening. The changes are small and unlikely to have clinical significance in most cases, though clinicians should be mindful of possible reasons, possibly repeating sub-modes and investigating players whose baseline scores change significantly after concussion. The findings do not necessitate a change in the sport’s concussion management policy.